2019
DOI: 10.12911/22998993/112489
|View full text |Cite
|
Sign up to set email alerts
|

Biogranulation and Physical Properties of Aerobic Granules in Reactors at Low Organic Loading Rate and with Powdered Ceramsite Added

Abstract: In wastewater treatment, aerobic granular sludge (AGS) technology is a relatively new alternative to the activated sludge method. The biogranulation of biomass ensues when appropriate environmental conditions in a reactor are ensured, and one of the factors determining this is the organic loading rate (OLR). As a literature review suggests, the optimal values of OLR for AGS technology are in the range of 2.50-7.50 g COD/(dm 3 •d), the aim of the work detailed here was to evaluate the impact of powdered ceramsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Additionally, other studies regarding the development of wastewater treatment technologies and the optimization of the processes have been carried out and implemented. They have concerned issues related to the development of technologies that use activated sludge in various forms [7][8][9][10][11]; the bioaugmentation of reactors [12,13], biofilm, and hybrid techniques [14,15]; and the preliminary preparation and pre-treatment of sewage sludge and back-side waters [16,17]. New research has also covered alternative technologies, e.g., sorption which may be used for the removal of a big amount of organic and inorganic pollutants and which can be used in conjunction with several techniques (such as flocculation-coagulation) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, other studies regarding the development of wastewater treatment technologies and the optimization of the processes have been carried out and implemented. They have concerned issues related to the development of technologies that use activated sludge in various forms [7][8][9][10][11]; the bioaugmentation of reactors [12,13], biofilm, and hybrid techniques [14,15]; and the preliminary preparation and pre-treatment of sewage sludge and back-side waters [16,17]. New research has also covered alternative technologies, e.g., sorption which may be used for the removal of a big amount of organic and inorganic pollutants and which can be used in conjunction with several techniques (such as flocculation-coagulation) [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The group of physical properties of aerobic biomass includes the morphology and size of granules, spatial structure, sedimentation properties, porosity, specific gravity, density of granules, water content and physical strength [4][5][6][7][8]. The physical parameters of granular biomass are important due to the stability of the granules obtained, but also given the nature of the biological processes by which wastewater is treated [9].…”
Section: Introductionmentioning
confidence: 99%
“…A number of materials from the first group were used, including powdered activated carbon (PAC) [21,22], dry sewage sludge micropowder [23], granular activated carbon (GAC) [24][25][26][27], and biochar [28]. The mineral materials used to date were zeolite [29], bivalve shell carrier [30,31], yellow earth [32], ceramsite [8,20] and basalt [17]. According the literature [20,23,27,31,32], adding such materials to a reactor results in an improvement of the sedimentation properties of the obtained aerobic granules, as well as allowing the acceleration of microorganism aggregation and the formation of mature granules in a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Most reports on successful granulation have shown that a high OLR is critical to the development and maturation of aerobic granules [ 7 , 8 , 9 ]. Higher OLR facilitates granule formation [ 9 , 10 , 11 , 12 ]. According to a literature review, the optimal OLR of a granular sequencing batch reactor (GSBR) is 2.50 g COD/(L∙d) [ 13 ] or should be in the range 2.50–7.50 g COD/(L∙d) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, research on improving AGS technology has involved chemical coagulants [ 17 ], dosage of granule fragments [ 18 , 19 ], and powdered materials, both mineral ( Table 1 ) [ 4 , 11 , 20 , 21 , 22 ] and organic [ 10 , 23 , 24 , 25 , 26 , 27 , 28 ]. It should be emphasized that in addition to the use of metal ions and flocculants, organic materials are most often described in the latest review articles [ 29 , 30 ], the subject of which concerns strategies implemented to improve the biogranulation process.…”
Section: Introductionmentioning
confidence: 99%